Pusat Warisan Budaya Melayu Riau Di Pekanbaru Dengan Pendekatan Arsitektur Kontemporer - Herdiman, Sepri; Aldy, Pedia; Hidayat, Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Riau’s Malay is one of many malay cultures in Southeast Asia. On the sidelines of the history of the Malay, it created many kingdom. So much produce cultural heritage that should be preserved. But the longer cultural heritage of the Malay increasingly drowned out by the times are so rapidly. That why need to create regional Riau Malay Heritage Centre is in preserving cultural heritage. Not only as a means of conservation of cultural heritage, this area also serves as a place of cultural tourism and small-scale industries. So as to increase financial artisans and art workers. Its design concept is Cluster Heritage, which means the incorporation of cultural heritage. Riau Malay culture that spread in Riau province has a diverse cultural heritage, including language, art, way of life, social and even traditional houses. Malay cultural diversity this is combined into a single site design. Cluster is applied to site, while Heritage take 3 basic forms of Malay house, lontik house, lipat kajang house adn limas house which transformed to building design. The need for contemporary architecture in the design area in maintaining the existence of the Malay cultural heritage facility in order to be able to compete with the rapid development of the environment surrounding the region infrastructure. Design elements of the Riau’s Malay Heritage Centre in the form of zoning, mass order, outdoor planning, mass formation, indoor planning and structure.Keyword: Riau’s Malay Heritage, Cluster Heritage, Contemporary Architecture